Perceptions of interprofessional teamwork in low‐acuity settings: a qualitative analysis. Issue 6 (June 2014) - van, Sandrijn M; O'Brien, Bridget C; Almeida, Sandra A; Adler, Shelley R
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at "discuss"